Afterword: Thoughts on Governance, Punctuation and Authoritarian Populism. Issue 1 (1st March 2023) - de Abreu, Maria José
Abstract: Inspired by key concerns of this collective project, this afterword article highlights two main aspects in the discussion of governance through suspension. The first aspect is how geographically widespread the rhetoric of 'indeterminacy' (as the fuel of the temporal medium of suspension) has become, soliciting analyses of differentiation across cultures and time. The second aspect relates to the politics of punctuated time in light of changes happening in our current culture of temporality. These two aspects integrate my interest in rethinking the classic concept of the (sovereign) decision conceived as separation from towards that of incision as cut through, particularly in light of rising expressions of authoritarian populism, globally, across regimes.